A study on awareness of college students about cryptocurrency and Its relation to Level of Education - Sudarshan D. Jadhav; Chavan Patil Sourabh Raghunath; WalandkarAshif Hamid; More Vaishali Anil (Universitas Pendidikan Indonesia (UPI), 2023)
Technology made many changes to the payment system. Students are more familiar with the technology. After the bitcoin boom in India, the mostly young generation are attracted to cryptocurrency. Cryptocurrency is decentralized and it is based on blockchain technology. Bitcoin, Ethereum, Cardano, Dogecoin, Litecoin, Bitcoin Cash, and Potcoin are more popular cryptocurrencies in India. The majority of investors are the age of between 18 and 24 years old. This study mainly focuses on the awareness of college students about cryptocurrency. This study also focuses on various factors that affected awareness of cryptocurrency. For this study, we collected 120 students’ responses. Samples were selected based on the non-probability snowball sampling method. The finding of this study is, that most respondents are aware through friends and social media about the cryptocurrency. And male respondents are more aware than female respondents. The higher level of educational qualification also impacts the high-level awareness of cryptocurrency. The majority of respondents are interested to invest in cryptocurrency.